Attitude towards Teaching Profession among the Prospective Teachers in Chennai District - L. , Maria Suganthi; K. , Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Teachers shoulder the responsibility of shaping the future of the nation. The future of the nation depends upon the skills and efficiency of the teachers. Teachers are given the other name as creator. They are the creators of philosophers, leaders, doctors, advocates, and many more. A teacher’s job is not at all that easy, and unless a high degree of professional qualities and commitment is inculcated in the teacher’s personality, the training program would remain incomplete. If teachers acquire professional competencies and commitment and if they are enabled and empowered to perform their multiple tasks in the classroom as well as in the school and community in a genuinely professional manner, then high-quality learning among students may result in cognitive, affective, and psychomotor areas of human development improving teaching performance through more effective teacher preparation; therefore, it is an essential ingredient in solving most educational problems. Educationists all over the world have started realizing that only securing enough teachers will not do; most important is securing the right type of teachers with the right type of knowledge, skills, attitudes, and competence. The effective attitudes and actions employed by teachers ultimately can make a positive difference in the lives of their students, and this belief will serve as the central focus of this paper. The present study consisted of 300 student teachers drawn randomly from different schools in Chennai. The Attitude towards Teaching Profession Scale and personal data sheet were used. t-test and ANOVA showed that there does not exist a difference with gender, teachers in the family, academic qualification, and age.